INFLUENCE OF DIELECTRIC CONSTANT (D), [H+] AND [SO4 2−] ON THE RATE OF REDOX REACTION BETWEEN TRIS (2,2′-BIPYRIDINE) IRON(II) AND CERIC SULPHATE IN AQUEOUS SULPHURIC ACID MEDIUM - Khattak, R.; Naqvi, I. I.; Farrukh, M. A. (Journal of Research (Science), 2007)
Kinetic of the redox reaction between tris (2,2′-bipyridine)iron(II) cation and ceric sulphate has been studied in aqueous sulphuric acid medium. Different methods were employed for the determination of order of reaction. The order of reaction is found to be first with respect to reductant however retarding effect of increasing initial concentration of oxidant is found. Influence of [H+], [SO42−] and dielectric constant (D) on the rate of redox reaction has also been studied. Increase in [H+] and dielectric constant of the medium retard the rate while enhancement of the [SO42−] accelerates the rate first and then the reaction goes towards retardation. Effects of [H+] and [SO42−] were studied by using acetic acid-sodium acetate buffer for the first one and varying ionic concentrations of the salt sodium sulphate for the latter one, whereas dielectric constant was varied by using 0%, 10% and 20% ethanol-water mixtures. Results of effects of each one of the factors i.e., H+, SO42− and dielectric constant (D) have been compared and on the basis of these factors, [Ce(SO4)32−] is suggested to be the active species of cerium(IV). However a rate law consistent with the observed kinetic data has also been derived supporting the proposed mechanism.